Impact of Global Trade Dynamics on the United States Rubber Industry - Natakam, Vineel Mouli; Nizamuddin, Md.; Tejani, Jayadip GhanshyamBhai; Yarlagadda, Vamsi Krishna; Sachani, Dipakkumar Kanubhai; Karanam, Raghunath Kashyap (American Journal of Trade and Policy, 2022)
This study looks at how global trade dynamics affect the rubber business in the United States, emphasizing how supply chain adaptation, trade regulations, and market trends affect industry competitiveness and prospects in the future. The study's primary goals are to evaluate supply chain adaptation techniques, examine potential future growth opportunities for the industry, and explore how trade policies affect market competitiveness. To acquire information about international trade trends and their consequences for the rubber business in the United States, a thorough examination of secondary data sources, such as government publications, industry reports, and scholarly journals, was conducted. The impact of globalization on trade patterns, the necessity of supply chain resilience through technology adoption and strategic partnerships, and the role of innovation and sustainability in boosting industry competitiveness are among the key conclusions. The policy implications underscore the necessity of equitable trade rules that foster transparency, minimize trade obstacles, and allocate resources toward technology and sustainable practices to bolster sector resilience. The research highlights the significance of cooperative endeavors between industry participants and policymakers in cultivating a favorable trade atmosphere for the sustainable economic growth of the rubber sector in the United States.
Keywords: Global Trade Dynamics; United States Rubber Industry; Trade Impact Analysis; Rubber Market Trends; Trade Policy Effects; Economic Globalization